Women, gender, and development : contemporary issues - Mahtab, Nazmunnessa (Dhaka : A. H. Development Pub. House ; Kolkata : Distributor in India, Paragon Enterprise, 2012)
With partial reference to women in development activities in Bangladesh.
Includes bibliographical references and index.
Keywords: Women in development; Feminism; Women in development -- Bangladesh